THE INFLUENCE OF EMPLOYEE ENGAGEMENT AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE - Annisa, Annisa; Apriani, Sindy; Kartono, Kartono (Penerbit Lafadz Jaya, 2024)
This research aims to analyze the influence of employee engagement and organizational culture on employee performance. The object of this research is the Cirebon City Regional Secretariat office. Data obtained through surveys by distributing questionnaires and interviews. The data analysis technique used is saturated sampling analysis, namely with a population of 122 employees and a sample of 72 employees. And the data was analyzed using SPSS (Statistical Package for the Social Sciences) version 24 for window. The research results show that Employee Engagement has a significant influence on Employee Performance. Organizational culture has a significant influence on employee performance. And there is an influence on Employee Engagement and Organizational Culture on Employee Performance.